Appendicular Diverticulum Mimicking Acute Appendicitis: A Case Report - D Karishmayadav; Ganesh Guru; Ramalakshmi .; K Barathiraja; Somanjeri Venkata Vidya Sagar (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Acute appendicitis is one of the most common surgical emergencies encountered in clinical practice. It typically presents with right iliac fossa pain, nausea, vomiting and leukocytosis and is often managed surgically with appendicectomy. Despite a wellestablished clinical presentation, several rare pathological entities can mimic acute appendicitis, posing diagnostic challenges for clinicians. Appendicular diverticulum is an uncommon condition characterised by sac-like protrusions of the appendiceal wall. The authors report a 44-year-old male who presented to the surgical Outpatient Department with abdominal pain for 20 days, associated with episodes of vomiting and intermittent fever. The pain was predominantly localised to the right iliac fossa and was described as intermittent rather than acute in onset. There was no history of similar episodes. The patient had no known co-morbidities such as diabetes mellitus or hypertension. The laboratory profile was within normal limits. The appendicular diverticulum was confirmed by histopathological and immunohistochemical tests without any evidence of neoplasia. The patient was advised to undergo periodic clinical surveillance, given the known association between appendicular diverticulum and appendiceal neoplasms. There was no evidence of any postoperative complication or recurrence. The present case highlights a rare presentation of appendicular diverticulum mimicking acute appendicitis. It emphasises the importance of histopathological evaluation and immunohistochemistry in all appendicectomy specimens.